The Visual Decision Maker: A recommendation system for collocated users - Drucker, Steven; Regan, Tim; Roseway, Asta; Lofstrom, Markus (Proceedings of the 2005 conference on Designing for User eXperience, 2005)
We present the Visual Decision Maker (VDM), an application that gives movie recommendations to groups of people sitting together. The VDM provides a TV like user experience: a stream of movie stills flows towards the center of the screen, and users press buttons on remote controls to vote on the currently selected movie. A collaborative filtering engine provides recommendations for each user and for the group as a whole based on the votes. Three principles guided our design of the VDM: shared focus, dynamic pacing, and encouraging conversations. In this paper we present the results of a four month public installation and a lab study showing how these design choices affected people's usage and people's experience of the VDM. Our results show that shared focus is important for users to feel that the group's tastes are represented in the recommendations.